THE APPLICATION OF SEMANTIC FEATURE ANALYSIS AS A STRATEGY TO ENRICH STUDENTS’ VOCABULARY - Akil, M. Ardhan; Rosida, Ana (Study Program of English Literature, 2018)
This research aimed at finding out whether or not significant improvement on students’ vocabulary after applying Semantic Feature Analysis. Pre-experimental design was applied in this research with one group pretest - posttest design. The population of this research was the second grade class of SMA Negeri 1 Majene, 2014/2015 academic year with 28 students as the samples. The researcher used simple random sampling technique in taking the samples. The research instrument used vocabulary test through written test using Semantic Feature Analysis Grid. The result of this research showed that the application of Semantic Feature Analysis in this research had significant influence in students’ vocabulary enrichment. It was proved by the improvement of mean score from 41,03 in pre-test to 72,71 in post-test. It was supported by the value of the t-test 18.7 which was greater than the value of t-table 1,703 the level of significance (p) = 0.05 and degree of freedom (n-1)=28.